2010
DOI: 10.1038/ejhg.2009.243
|View full text |Cite
|
Sign up to set email alerts
|

Additional evidence to support the role of a common variant near the complement factor I gene in susceptibility to age-related macular degeneration

Abstract: Recessive (1 df) 0.28 (0.11-0.69) 0.0035 (0.0022)Abbreviations: df, degree of freedom; CI, confidence interval; OR het and OR hom , odds ratio for heterozygote and rare homozygote, respectively, estimated by unconditional logistic regression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
23
2
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 4 publications
3
23
2
1
Order By: Relevance
“…We found genotypic associations both in the additive model (OR, 1.30; 95% CI, 1.03-1.63; P ¼ 0.025) and dominant model (OR, 1.42; 95% CI, 1.03-1.97; P ¼ 0.033). The results of a previous Japanese study 18 were in favor of the recessive model (P ¼ 0.0035 compared with P ¼ 0.036 in the additive model), whereas in our study, the additive model was found to be the best-fitting model of inheritance with the lowest AIC among the three models (Table 2). Furthermore, our study was well-powered because the current sample size demonstrated 490% statistical power to detect association significance (OR, 1.33).…”
contrasting
confidence: 47%
See 2 more Smart Citations
“…We found genotypic associations both in the additive model (OR, 1.30; 95% CI, 1.03-1.63; P ¼ 0.025) and dominant model (OR, 1.42; 95% CI, 1.03-1.97; P ¼ 0.033). The results of a previous Japanese study 18 were in favor of the recessive model (P ¼ 0.0035 compared with P ¼ 0.036 in the additive model), whereas in our study, the additive model was found to be the best-fitting model of inheritance with the lowest AIC among the three models (Table 2). Furthermore, our study was well-powered because the current sample size demonstrated 490% statistical power to detect association significance (OR, 1.33).…”
contrasting
confidence: 47%
“…14 In addition, the C allele of rs10033900 has been commonly identified as a protective allele against AMD in genetic studies. 8,14,17,18 However, there remains debate as to whether rs10033900 contributes to AMD susceptibility, due to contradicting evidence published in this journal. [18][19][20] For example, Ennis et al 20 confirmed the association between the CFI region and AMD susceptibility in a UK cohort, although rs10033900 showed no association with AMD.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Non-coding polymorphisms adjacent to the gene and in an intron of CFI are associated with altered risk of AMD. 70 The associations have been independently replicated, 71,72 but no functional cause of the association has been found. Whether variants in the promoter region affect expression or whether undiscovered coding changes in the gene are responsible remains unknown.…”
Section: Genetic Variants Of Complement Genes Associated With Amd Andmentioning
confidence: 87%
“…The association signal extended over a region of about 175 kb, the most associated variant (Po10 À7 ) being the SNP rs10033900 near the complement factor I (CFI) gene. Two replication studies 2,3 published also in this journal provided some additional support for an AMD susceptibility locus in this region. In the course of candidate gene studies of AMD, we had previously investigated SNPs spanning CFI including rs10033900 in a UK case-control sample, which shows the expected associations with the wellestablished AMD-susceptibility loci CFH, ARMS2, CFB and C3.…”
mentioning
confidence: 98%